Variations in EUV Irradiance: Comparison between LYRA, ESP, and SWAP Integrated Flux - Mehmet Sarp Yalim; Stefaan Poedts (Advances in Astronomy)
The Sun Watcher Using Active Pixel System Detector and Image Processing (SWAP) telescope and Large Yield Radiometer (LYRA) are the two Sun observation instruments on-board PROBA2. SWAP extreme ultraviolet images, if presented in terms of the integrated flux over solar disk, in general, correlate well with LYRA channel 2–4 (zirconium filter) and channels QD and 18 of EVE/ESP on-board SDO between 2010 and 2013. Hence, SWAP can be considered as an additional radiometric channel. We compare in detail LYRA channel 2–4 and SWAP integrated flux in July 2010 and in particular during the solar eclipse that occurred on July 11, 2010. During this eclipse, the discrepancy between the two data channels can be explained to be related to the occultation of active region 11087 by the Moon. In the second half of July 2010, LYRA channel 2–4 and SWAP integrated flux deviate from each other, but these differences can also be explained in terms of features appearing on the solar disk such as coronal holes and active regions. By additionally comparing with timeline of EVE/ESP, we can preliminarily interpret these differences in terms of the difference between the broad bandpass of LYRA channel 2–4 and the, relatively speaking, narrower bandpass of SWAP.